PLAC8 is an innovative biomarker for immunotherapy participating in remodeling the immune microenvironment of renal clear cell carcinoma - Sun, Xu; Liu, Zhanpeng; Yu, Qian; Chen, Yinwei; Sun, Yunwen; Zhu, Qingyi; Yang, Jian; Jiang, Rongjiang (Frontiers in Oncology, 2023)
Background: PLAC8 has been identified in the progression of various cancers by inducing tumorigenesis, immune response, chemotherapy resistance and metastasis. Nevertheless, the precise biological function of PLAC8 in renal cancer remains unknown. Methods: We obtained the expression profile and associated clinical characteristics of patients diagnosed with clear cell renal cell carcinoma (ccRCC) from The Cancer Genome Atlas database. The biological behavior of specific cell lines was detected using Cell Counting Kit-8 (CCK-8), colony formation, and 5-ethynyl-2'-deoxyuridine (EdU) assay. A prognostic model was constructed based on PLAC8-related molecules through a machine-learning algorithm. Results: We observed overexpression of PLAC8 in ccRCC patients. In addition, PLAC8 has been identified as being linked to unfavorable clinical characteristics and adverse prognosis outcomes. Biological enrichment analysis revealed the potential involvement of PLAC8 in cell cycle checkpoints, mitotic phase transformation, immunotherapy-predicted and reactive oxygen species (ROS) related pathways. In addition, immune analyses showed that PLAC8 was involved in remodeling the tumor microenvironment (TME) and affecting the effect of immunotherapy in ccRCC patients. In vitro experiments demonstrated a significant reduction in the proliferation, invasion and migration of renal cancer cells following the knockdown of PLAC8. Finally, LASSO logistics regression was applied to construct a prognosis model, which presented a favorable prediction ability on the prognosis of ccRCC.Our results implied that PLAC8 may be a novel immunotherapy biomarker of ccRCC, which is a crucial molecule in remodeling the cancer microenvironment. PLAC8 can predict immunotherapy response and is expected to guide precise treatment.